Qualitative Process Evaluation of a Community-based Culturally-tailored Lifestyle Intervention for Underserved South Asians - Jayaprakash, Manasi (Health Promot Pract, 2016)
INTRODUCTION: There are few examples of effective cardiovascular disease (CVD) prevention interventions for South Asians (SAs). We describe the results of a process evaluation of the South Asian Heart Lifestyle Intervention (SAHELI) for medically-underserved SAs implemented at a community-based organization (CBO) using community-based participatory research (CBPR) methods and a randomized control design (n=63). METHODS: Interviews were conducted with 23 intervention participants and 5 study staff using a semi-structured interview guide focused on participant and staff perceptions about the intervention’s feasibility and efficacy. Data was thematically analyzed. RESULTS: Intervention success was attributed to: trusted CBO setting, culturally concordant study staff and culturally-tailored experiential activities. Participants said that these activities helped increase knowledge and behavior change. Some participants, especially men, found that self-monitoring with pedometers, helped motivate increased physical activity. Participants said that the intervention could be strengthened by greater family involvement and by providing women-only exercise classes. Staff identified the need to reduce participant burden due to multi-component intervention and agreed that the CBO needed greater financial resources to address participant barriers. CONCLUSION: Community-based delivery and cultural-adaptation of an evidence-based lifestyle intervention were effective and essential components for reaching and retaining medically underserved SAs in a CVD prevention intervention study.